Mutations and prognosis in myelodysplastic syndromes: karyotype‐adjusted analysis of targeted sequencing in 300 consecutive cases and development of a genetic risk model. Issue 5 (24th February 2018) - Gangat, Naseema; Mudireddy, Mythri; Lasho, Terra L.; Finke, Christy M.; Nicolosi, Maura; Szuber, Natasha; Patnaik, Mrinal M.; Pardanani, Animesh; Hanson, Curtis A.; Ketterling, Rhett P.; Tefferi, Ayalew
Abstract: To develop a genetic risk model for primary myelodysplastic syndromes (MDS), we queried the prognostic significance of next‐generation sequencing (NGS)‐derived mutations, in the context of the Mayo cytogenetic risk stratification, which includes high‐risk (monosomal karyotype; MK), intermediate‐risk (non‐MK, classified as intermediate/poor/very poor, per the revised international prognostic scoring system; IPSS‐R), and low‐risk (classified as good/very good, per IPSS‐R). Univariate analysis in 300 consecutive patients with primary MDS identified TP53, RUNX1, U2AF1, ASXL1, EZH2, and SRSF2 mutations as "unfavorable" and SF3B1 as "favorable" risk factors for survival; for the purposes of the current study, the absence of SF3B1 mutation was accordingly dubbed as an "adverse" mutation. Analysis adjusted for age and MK, based on our previous observation of significant clustering between MK and TP53 mutations, confirmed independent prognostic contribution from RUNX1, ASXL1, and SF3B1 mutations. Multivariable analysis that included age, the Mayo cytogenetics risk model and the number of adverse mutations resulted in HRs (95% CI) of 5.3 (2.5‐10.3) for presence of three adverse mutations, 2.4 (1.6‐3.7) for presence of two adverse mutations, 1.5 (1.02‐2.2) for presence of one adverse mutation, 5.6 (3.4‐9.1) for high‐risk karyotype, 1.5 (1.1‐2.2) for intermediate‐risk karyotype and 2.4 (1.8‐3.3) for age >70 years; HR‐weighted risk point assignment generated a three‐tiered genetic risk model: high ( N  = 65; 5‐year survival 2%), intermediate ( N  = 100; 5‐year survival 18%), and low ( N  = 135; 5‐year survival 56%). The current study provides a practically simple risk model in MDS that is based on age, karyotype, and mutations only.